Pengaruh Penyajian Informasi Pajak dalam Kondisi Ketidakpastian terhadap Perilaku Kepatuhan Pajak - Mayar Afriyenti; Fauzan Misra (Jurnal Akuntansi dan Governance Andalas, 2015)
Reinforcement paradigm is assumed as an incomplete paradigm to increasing taxpayer compliance. This paradigm should be supported by other paradigm, i.e. service paradigm. Reinforcement paradigm is too emphasized on tax audit and penalty charges. It needs high tax audit frequencies and, as consequence, very costly. Recent tendencies show that its intensity decreases. In adverse, service paradigm is adopted in many countries’ current tax reform, including Indonesia. This paradigm recognizes the importance role of “kinder” and “gentler” tax administration. This research aims to examine the influence of information provision as a service mechanism toward taxpayer compliance. This experiment consist of two treatments (i.e. uncertainty and information provision) and a baseline. Data is analyzed using one-way Anova. The result of research shows tax compliance declines when taxpayer faces uncertainty. This condition then off-set by information provision. This findings suggest that service paradigm is a good complement to reinforcement paradigm.